A Study of Rice Husk Ash on the Strength of Concrete - Nurul Izzati Othman; MOHD SUFYAN ABDULLAH (Progress in Engineering Application and Technology, 2025)
Ordinary Portland Cement (OPC) is a crucial component in concrete however its manufacture results in high carbon emissions. This paper present the rice husk ash (RHA) potential as a partial replacement for 8%, 9%, 10%, 11% and 12% of cement. RHA contains high silica content which enhances its reactivity and makes it suitable for use in cement based materials. It aim to investigate the degree of workability and the compressive strength of concrete. The degree of workability was measured through the use of slump test and compressive strength test were determined by testing the concrete cubes after 7 and 28 days of curing. A total of 36 concrete cube were casted and tested to determine the compressive strength. The results showed the slump values ranged from 54mm(0% RHA) to 34mm(12% RHA) indicate that workability decreased consistently with increased RHA percentage. However, none of the RHA reached the targeted grade 25 strength of 25 Mpa after 28 days and the compressive strength of all RHA were found at 9% replacement. It is recommended to do better in processing of RHA into cement like particles and also design a new optimum proportion for future study.